Implementasi Program Tahfizh Qur’an Di PAUD Inklusif Dengan Model HOTS - Enung Nugraha (UIN Sultan Maulana Hasanudin Banten, 2020)
Introducting Al-Qur'an has done by cooperation of parents and teachers which tahfizh Al-Qur'an interacting on daily consolidated. Tahfizh Qur'an is a religious program to improve children's concentration and learning outcomes. HOTS model approach an important role. The study to determine the implementation tahfizh Qur'an program in early childhood by higher order thinking skills (HOTS) model. The method used literature study approach. The tahfizh program in early childhood is part of religious and character education so that children memorize, deepen meaning and empathy, get used to at school and home. Teachers can apply higher order thinking skills learning models, not only evaluating the memorization of the Qur'an but until students act to do something and even become used to it. Implementatign of tahfizh Qur'an program in early childhood using HOTS model is important for teachers at school and guided by parents at home so habituation besides increasing concentration also fosters empathy.